LEXICAL-SEMANTIC AND LINGUACULTURAL FEATURES OF ENGLISH-UZBEK DESIGN AND PAINTING TERMS - Raxmanova Dilorom Yuldosh qizi (Journals Park Publishing, 2022)
Terminology is a set of words and phrases used in linguistics to express specific concepts and names related to a particular field of science, it is an independent sector of any national language, closely related to professional activities. This article discusses design and painting terms as well as lexical-semantic and linguacultural features of them.
Keywords: term, terminology, design terms, painting terms, lexical-semantic features, linguacultural features